Acoustic parameters of swallowing using Doppler Sonar – DeglutiSom software: a contribution to the evaluation in adults - Cárdenas-Camayo, Yolanda; Muñoz-Zambrano, Isabel; Cháves-Mejía, Ariana Vanessa; Tobar-Bonilla, Jeniffer (Revista de Investigación en Logopedia, 2024)
With the advance of technology, mechanisms are created that facilitate and optimize the evaluation process of the acoustic parameters of swallowing, but it is necessary for the measurement to be reliable, considering normality patterns. The objective of this study was to determine the acoustic parameters of frequency, intensity and duration of swallowing with Doppler sonar and Deglutisom software in an adult population in Popayán. The methodology was quantitative descriptive and cross-sectional. Swallowing was evaluated in 115 adults and 31 older adults, normotypic subjects selected non-randomly, with the ingestion of three consistencies: proper fluid, clear liquid and pasty. It was observed that for the "adult" group the average values (x̄) of the parameters that indicated to be within normality were: in frequency between 760.44 Hz to 766.92 Hz, intensity ranged between 99.99 to 100 dB; and in duration between 0.90 to 0.97 seconds. In the "older adults" the normality values in frequency parameter were between 765.93 to 763.41 Hz, intensity between 99.64 to 100 dB and duration over ̄1.01 to 1.11 seconds in all three consistencies. The acoustic parameters are similar between the same groups of "adults" and older adults; however, there were significant differences when comparing them, especially in the duration parameter (sec) (p
Keywords: acoustic parameters; swallowing; swallowing disorders; adult; doppler sonar; technology